Effect of plasma treatment on the properties of Arundo Donax L. leaf fibres and its bio-based epoxy composites: A preliminary study. (1st June 2016) - Scalici, T.; Fiore, V.; Valenza, A.
Abstract: A preliminary investigation about the effect of plasma treatment on the properties of natural fibres extracted from the leaf of the giant reed Arundo Donax L. and their compatibility with a bio-based epoxy resin is performed. To this aim, the influence of plasma treatment on the functional groups and on the thermal behaviour of fibre were investigated using Fourier transform infrared spectroscopy and thermogravimetric analysis. Moreover, the mechanical characterization of fibres was performed through fibre tensile tests. Short randomly oriented fibres/bio-based epoxy composites were manufactured by hand lay-up method followed by compression moulding, varying both fibres weight content and length. The influence of plasma treatment was evaluated by performing quasi-static and dynamic mechanical tests on the composites. Changes in the surface functional groups are obtained whereas neither the thermal stability nor the tensile properties of fibres are influenced by plasma treatment. Characterizations of the composites showed remarkable enhancements of mechanical properties, indicating that plasma treatment improves fibre/matrix adhesion. SEM micrographs showed that the resin better adheres around treated fibres compared to untreated ones.